Perancangan Pemodelan Sistem Penentuan Keputusan Untuk Pemilihan Jurusan Menggunakan Metode Perbandingan Eksponensial (MPE) Perguruan Tinggi Di Jawa Barat - Redaksi Tim Jurnal (PETIR, 2017)
Information Technology is providing a lot of convenience that can be felt by human life. One example of the era of information technology is the birth of computers in the life of society .. Computers are now perceived to provide a lot of mamfaat that can not be separated from human life. In every company or institution, in its data processing has been applied by using computer. Therefore the computer can be made aspects of decision support is good and appropriate in taking a decision. Particularly related institutions ie colleges are the most important thing when they apply teaching and learning activities between lecturers and students. This is very important if the college wants to produce a good graduate and achievement, then the college should take the lead if you want to achieve it. Things that can be addressed is a new student admissions system kesetiap public and private universities in Indonesia. Why is that, with the existence of a computerized system it will provide convenience in determining the choice of majors to choose, because one of the most important factor is how the prospective students can determine the choice according to their interests and talents. So that in their teaching and learning activities will be optimal, there will be no complaints that cause the student has a mind to not continue his studies. Then it should be time the college to change the existing system by making an information system for the selection of majors for prospective students in accordance with the desired department. From this case then as a researcher wants to provide input by presenting a new innovation that is by building a system of election information majors for public and private universities in Indonesia.